Education of a team in fencing: the possibilities of an environmental approach and art pedagogy - Lobanov V.V. ,; Revyakina V.I. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the features and possibilities of using a specialized environment for educating a sports team using art pedagogy methods. Methods and structure of the study. The study was carried out using the example of teams whose core activity is fencing. The authors proceed from the idea that the aestheticization of the competitive process is not a sufficient basis for the effective education of a team in terms of the ideas of art pedagogy, as a result of which targeted managerial and organizational-pedagogical efforts are necessary to create an aesthetically valuable subject-spatial content of the training process. Results and conclusions. An analysis of the practice of sports groups (“Victoria”, “Musketeers of Setuni”, “Florette”, “Musketeer”) made it possible to establish the educational feasibility of including students both in the existing specialized environment, aesthetically reflecting sports activity, and in the processes of creating such an environment, which as a result acquires unique proportionality to a specific team. Also, as a result of the study, it was revealed that the universalization of sports facilities reduces the effectiveness of using the environmental approach and methods of art pedagogy for educational work in sports teams.